(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. Financial technologies play a crucial role in socio-ecological-economic development by automating various processes across all sectors and increasing service accessibility not only in large cities but also in every corner of the country. The use of remote customer service channels reduces labor and associated costs, promoting more efficient resource utilization. FinTech supports the growth of financial markets and serves as a vital tool for optimizing both the everyday lives of individuals and the functioning of the entire ecosystem. These technologies significantly facilitate the formation of connections between different sectors, accelerating the attainment of economic, social, technological, political, and other benefits. FinTech not only fosters economic growth but also supports sustainable development by enhancing social inclusiveness and promoting ecological sustainability through more efficient resource use and reduction of the carbon footprint. The purpose of the article. It is necessary to investigate the theoretical and applied understanding of AI in Fintech as a driver of socio-ecological-economic development. Results. Trends in AI, considering sustainable development and financial technologies, highlight the following key directions: Green AI (energy-efficient algorithms; energy consumption optimization); Ethical and Transparent AI (ethical principles; explainability); Inclusive Financial Technologies (financial inclusion; personalized financial services); Innovations in Lending and Risk Management (creditworthiness analysis; risk forecasting); Intelligent Investment Platforms (robo-advisors; micro-investments); Cybersecurity (threat detection; behavior analysis); Sustainable Development through Financial Technologies (investing in sustainable development; impact monitoring). Therefore, it can be argued that the integration of artificial intelligence in financial technologies not only drives innovation in financial services but also upholds the principles of sustainable development, ensuring ethical, inclusive, and efficient practices. Conclusions. Financial technologies are rapidly evolving, stimulating the emergence of diverse services, including internet payments, lending through distributed ledgers, and mobile money transfers. Key directions in the development of financial technologies include fraud protection, business interchanges, and adaptation to regulations, opening up new opportunities for all consumer categories. Transformational trends in fintech innovations significantly impact Ukraine’s financial sector, expanding the accessibility of financial services and enhancing the efficiency of financial companies. It is necessary to ensure the creation of appropriate legislative and regulatory environments to guarantee the security and stability of the financial sector in the face of rapid development of digital technologies. The application of artificial intelligence in the financial sector is defined by key directions such as green AI, ethical and transparent AI, fostering innovation and sustainable development, increasing the efficiency and accessibility of financial services.